2011
DOI: 10.1074/jbc.m110.106922
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Estrogen Regulation of PEMT Results in Choline Deficiency-associated Liver Dysfunction

Abstract: When dietary choline is restricted, most men and postmenopausal women develop multiorgan dysfunction marked by hepatic steatosis (choline deficiency syndrome (CDS)). However, a significant subset of premenopausal women is protected from CDS. Because hepatic PEMT (phosphatidylethanolamine N-methyltransferase) catalyzes de novo biosynthesis of choline and this gene is under estrogenic control, we hypothesized that there are SNPs in PEMT that disrupt the hormonal regulation of PEMT and thereby put women at risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…Last, we did not genotypes these subjects. The variation in genes known to affect the choline synthesis pathway may more specifically identify individuals susceptible to choline deficiency or for whom choline supplementation may have a beneficial effect (20)(21)(22)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Last, we did not genotypes these subjects. The variation in genes known to affect the choline synthesis pathway may more specifically identify individuals susceptible to choline deficiency or for whom choline supplementation may have a beneficial effect (20)(21)(22)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 98%
“…This differential response has been hypothesized to arise from an estrogen-response element in the upstream region of the PEMT gene, which is an enzyme in one of the choline biosynthetic pathways (20). Genome-association studies have demonstrated susceptibility to choline deficiency with single nucleotide polymorphisms in this gene (20)(21)(22). It has also been shown that PEMT gene expression and enzyme activity are inducible on estrogen exposure in mouse and human hepatocytes (23).…”
Section: Introductionmentioning
confidence: 96%
“…Bioinformatics systems have shown that estrogens infl uence phosphatidylethanolamine N-methyltransferase (PEMT) gene expression, increasing the level and the activity of this enzyme. PEMT promoters in humans and rodents contain similar regions with 3 estrogen regulatory factors recognized as estrogen response elements [170][171][172][173] .…”
Section: Choline-estrogen Relationmentioning
confidence: 99%
“…In 1991, we reported that men fed defined diets low in choline content developed fatty liver and liver damage that resolved when choline was reinstated in the diet (46). In subsequent studies that included women, we found that premenopausal women often did not develop organ dysfunction when deprived of dietary choline, and this was because estrogen induces the gene ( PEMT ) responsible for de novo biosynthesis of phosphatidylcholine in liver (phosphatidylcholine serves as a source for choline) (47, 48). The subpopulation of premenopausal women who did develop choline deficiency when fed a low choline diet usually had a genetic variation (SNP) in PEMT that abrogated the estrogen responsiveness of this gene (47).…”
Section: From Acetylcholine To Proving the Human Requirement For Cholinementioning
confidence: 99%
“…In subsequent studies that included women, we found that premenopausal women often did not develop organ dysfunction when deprived of dietary choline, and this was because estrogen induces the gene ( PEMT ) responsible for de novo biosynthesis of phosphatidylcholine in liver (phosphatidylcholine serves as a source for choline) (47, 48). The subpopulation of premenopausal women who did develop choline deficiency when fed a low choline diet usually had a genetic variation (SNP) in PEMT that abrogated the estrogen responsiveness of this gene (47). Despite the resistance to choline deficiency seen in young women, almost all men and postmenopausal women developed fatty liver, liver damage, and/or muscle damage when fed a low choline diet, and this resolved when choline was restored in the diet (48).…”
Section: From Acetylcholine To Proving the Human Requirement For Cholinementioning
confidence: 99%